Smart campus: definition, framework, technologies, and services. Issue 1 (10th March 2020) - Dong, Zhao Yang; Zhang, Yuchen; Yip, Christine; Swift, Sharon; Beswick, Kim
Abstract : As the high‐end form of a smart education system, the smart campus has received increasing research attention over the world. Owing to the multidisciplinary nature of the smart campus, the existing research is mostly one‐ended on either the state‐or‐the‐art technologies or the innovative education concepts but lacks a deep fusion view on them and omits the smart campus implication on other smart city domains. This study highlights the interdisciplinary view on smart campus. Based on an integral review on the supporting technologies and existing smart campus propositions, a human‐centred learning‐oriented smart campus is envisaged, defined and framed up, primarily aiming at meeting stakeholders' interests and elevating educational performance in pace of the technology development, as well as discussing the interdisciplinary factors that either promote or constrain the smart campus revolution. The expected contribution throughout this study is to provide a benchmark reference of a smart campus for international educational providers, government, and technological companies providing such services.